2021
DOI: 10.1007/s13679-020-00421-x
|View full text |Cite|
|
Sign up to set email alerts
|

An Exploration of the Role of Sugar-Sweetened Beverage in Promoting Obesity and Health Disparities

Abstract: Purpose of Review The mechanistic role of sugar-sweetened beverage (SSB) in the etiology of obesity is undetermined. We address whether, compared to other foods, does consumption of SSB (1) automatically lead to failure to compensate for the energy it contains? (2) fail to elicit homeostatic hormone responses? (3) promote hedonic eating through activation of the brain's reward pathways? We followed the evidence to address: (4) Would restriction of targeted marketing of SSB and other unhealthy foods to vulnerab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 145 publications
0
13
0
Order By: Relevance
“…Added sugars in the diet contribute to the overall energy density of diets and may increase a positive energy balance [48]. The sugar-sweetened beverage is a potential risk factor for overweight in children and adolescents [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Added sugars in the diet contribute to the overall energy density of diets and may increase a positive energy balance [48]. The sugar-sweetened beverage is a potential risk factor for overweight in children and adolescents [49], [50].…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, the intake of SSB has been decreasing in recent years [ 48 ]. However, more detailed analysis has shown that there are both regional and sociodemographic differences in SSB consumption patterns.…”
Section: Intake Of Sweetened Beveragesmentioning
confidence: 99%
“…Increasing evidence shows that unrestricted consumption of high-sugar food and beverages within the Western Diet might be linked to the increased obesity epidemic ( Stanhope, 2016 ; Johnson et al, 2017 ; Freeman et al, 2018 ; Yoshida and Simoes, 2018 ; Sigala and Stanhope, 2021 ). A strong association between attention-deficits/hyperactivity disorders (ADHD) and overweight/obesity have further been revealed ( Altfas, 2002 ; Strimas et al, 2008 ; Cortese et al, 2016 ; Cortese, 2019 ).…”
Section: Introductionmentioning
confidence: 99%